Strengthening the Pedagogical Competence of Physics Teachers through Training in Making Recycled Learning Media Based on the Environment and Local Wisdom of Trenggalek - Satriawan, Muhammad; Sucahyo, Imam; Anggaryani, Mita; Kholiq, Abd.; Saputra, Oka; Habibbulloh, Muhammad (Journal of Dedication in Community, 2025)
This community service activity aims to improve the pedagogical competence of physics teachers in Trenggalek Regency through training in the creation of environmentally friendly, locally-based learning media based on used materials. Problems faced by teachers include limited laboratory facilities, a lack of creativity in creating teaching aids, and the lack of integration of local cultural potential, such as Reog Kendang, into physics learning. The activity methods include participatory training, hands-on practice in making teaching aids, and the preparation of Student Worksheets (LKPD) based on Problem-Based Learning (PBL). The results of the activity showed a significant increase in teachers' ability to design contextual teaching aids; 100% of participants experienced an increase in their understanding of the concept of sound, and 90% expressed satisfaction with the training results. The resulting products include PVC resonators, mini speakers made from used cans, and sound intensity measuring devices using an Android application. This activity not only fosters teacher creativity but also environmental awareness and the preservation of local culture. This training model is worthy of replication to support the implementation of the Independent Curriculum and SDGs 4 (Quality Education) and SDGs 12 (Sustainable Consumption and Production).